Committees of reality intra-hospital of organ and tissues donation in the State of Goiás - Saba, Eliana Nadim; Almeida, Clayton Gonçalves de; Paglione, Heloisa Barboza; Barreto, Regiane Aparecida Santos Soares; Roza, Bartira Aguiar (Brazilian Journal of Transplantation, 2017)
Introduction: Intra-hospital Organ and Tissue Donation Commissions (CIHDOTTs) were created to articulate the identification of potential donors and the process of organ procurement in hospitals. Purpose: To identify the sociodemographic profiling, self-perception and difficulties exposed by professionals that take part of the CIHDOTTs. Material and method: Exploratory research of qualitative and quantitative nature, carried out in the CIHDOTT of the three largest hospitals in the state of Goi s. Results: A minority perceived that they experienced in a family interview (15%), to perform the organ recruitment (16%), to maintain the potential donor (19%) and to progress in reporting the brain death (21%). The perception of 54% of the professionals regarding the view of the board on their work was unsatisfactory. The difficulties identified were: lack of knowledge (33%), lack of motivation (19%); lack of training (29%) and difficulty in defining functions between CIHDOTT and CNCDO (24%). They identified the need for permanent education (67%) and exclusive staff for the CIHDOTT (20%).Conclusion: Professionals perceived themselves as inexperienced to performa in CIHDOTT and the need for training and an exclusive team.